Perfil clínico y complicaciones del síndrome nefrótico en el Servicio de Pediatría del Hospital del MINSA, Iquitos 2022 - Mendoza Llanca, Fabiola Esmeralda (2025)
The objective of the study was to determine the association between the clinical profile and complications of nephrotic syndrome in the Pediatric Service of the Felipe Arriola Iglesias Regional Hospital of Loreto 2022. The method used was quantitative, descriptive, analytical, non-experimental retrospective, and the population consisted of 13 patients. The most important results were: Regarding age, the mean was 5.69 years, standard deviation of 4.92, the minimum age being 6 months and maximum age 14 years. Regarding sex, 38.5% were female and 61.5% were male. Regarding origin, 46.2% of children were from rural areas and 53.8% from urban areas. Regarding the clinical profile, of the total of 13 (100%) children who made up the sample, they presented: proteinuria 92.3%, edema 84.6%, fever 69.2%, abdominal distension 61.5%, dyspnea 30.8%, diarrhea 23.1%. The complications found were: of the total of 13 children in the study, 11 (84.6%) presented Acute Renal Failure, and 2 (15.4%) presented Cushing's Syndrome. No children presented Chronic Renal Failure. The comparative measure of odds ratio was applied in the study, obtaining a corrected value of 1.4. The Haldane-Anscombe technique was used, with a 95% confidence interval (CI), the lower limit of which was 0.049 and the upper limit of 45.7, p < 0.05, and an effect size of 0.122. The conclusion was that there was a correlation between the variables: edema, fever, abdominal distension, and proteinuria with acute renal failure, thus approving the study hypothesis.